PENINGKATAN KOMPETENSI KEJURUAN TEKNOLOGI OTOMOTIF BAGI GURU DAN SISWA PROGRAM STUDI TEKNIK OTOMOTIF SMK NEGERI DAN SWASTA DI KABUPATEN SOLOK MELALUI PROGRAM IPTEKS BAGI MASYARAKAT (IbM) - Toto Sugiarto; Bahrul Amin; Wakhinuddin Wakhinuddin (PAKAR Pendidikan, 2018)
Vocational High School aims to be able to prepare creative learners, master the science and technology, and have competence in accordance with the demands of the world of work. The quality of SMK graduates is not only determined by individual self-sufficiency factors, but the task is determined by outside tactics, one of which is the education that can prepare the graduates of the two demands for work. Science Program for Communities (IbM) aims to provide automotive technology training for teachers and students of SMK Negeri and Swasta in Solok district, IbM activities. The Vocational Competence Enhancement of Automotive Technology for Teachers and Students of SMK, it can increase knowledge and skills of trainers 13.88% in the the major, Automotive Technology.